Analgesic Effect of Caudal Bupivacaine with or without Clonidine in Pediatric Patient - Khakurel, Sharad; Sapkota, Shanta; Karki, Anuj Jung (Journal of Nepal Health Research Council, 2019)
Background: Caudal analgesia has long been the cornerstone to successful pain management in children undergoing abdominal and lower limb surgeries. Its analgesic duration with single shot injection is however limited. So adjuvants are used with local anesthetics in an attempt to increase the duration of caudal analgesia. This study aims to investigate the duration of analgesia provided by Clonidine when added to caudal Bupivacaine.Methods: A randomized, double blinded, comparative study was conducted on 64 patients, aged two to seven years, scheduled for unilateral inguinal hernia repair. Patients were randomly allocated into two groups of 32 each, with group A receiving bupivacaine two milligram/kilogram and group B receiving bupivacaine two milligram/kilogram with one microgram/kilogramclonidine, (total volume of injectate was one milliliter/kilogram). Duration of analgesia, hemodynamic response and adverse effects, if any were noted.Results: Mean duration of analgesia in group A was 264.12 ± 68.77 minutes and in group B was 520 ± 57.37 minutes, p-value <0.001.Incidence of vomiting was 9% in group A compared to 6% in group B.Conclusions: Clonidineas an adjuvant to caudal bupivacaine prolongs the duration of analgesia without increasing the adverse effects.Keywords: Bupivacaine; caudal analgesia; clonidine;pediatric.